ANALISIS PENGARUH STRUKTUR PASAR, BEBAN NON BUNGA, EKUITAS, DAN ASET LIKUID TERHADAP MARGIN BUNGA BERSIH PADA BANK UMUM YANG LISTING DI BURSA EFEK INDONESIA - Hardi Nata Purba; Syarief Fauzie (Departemen Ekonomi Pembangunan USU, 2014)
This research aim to obtain empirical evidence about the effect of market structure, non-interest expense, equity and liquid asset to net interest margin on commercial banks listed on the Indonesia Stock Exchange for period 2007-2011. In this research, the data used is the data of 11 commercial banks were selected through purposive sampling with criteria (1) commercial banks that are actively listed on the Indonesia Stock Exchange for period 2007-2011. (2) Commercial banks that consistently publishes annual financial statements for the period of 2007-2011. (3) Commercial banks that meet indicator dependent variable and the independent variables during the period of 2007-2011. The data is analyzed using panel data with multiple linear regression method with fixed effect model (FEM) are graded according to this research because this model has no intercept equation is constant or there are differences in each individual. Before analyzing the data, first Normality Test and Hausman test to determine the normality of the data and to determine whether the fixed effect model suitable for use in this study. Further processing of the data were performed using the Eviews 5.Results of this research found that simultaneous f-statistics test that variables of market structure, non-interest expense, equity and liquid asset have a significant effect on net interest margin at 95% confidence level, while it is partially based on t- statistics test concluded that the variables of market structure and equity had a positive effect and no significant on the net interest margin at the 95% confidence level. Non-interest expense variable has a positive and significant effect on net interest margin and the liquid assets variable has a negative and significant effect on the net interest margin at the 95% confidence level. Additionally determination coefficient indicates that the variable of market structure, non-interest expense, equity and liquid asset are able to explain the variable net interest margin on commercial banks listed on the Indonesia Stock Exchange amounted to 87.79%.Key words: Net Interest Margin, Market Structure, Non-Interest Expense, Equity, and Liquid Asset.